Arturo Salazar Bondy and teaching philosophy - Romero Meza, Alex (2014)
The paper will discuss the nature of philosophy teaching in what has been called Augusto Salazar Bondy Education and the philosophy of the crisis. The plight of Peruvian culture, as exemplified by education and a philosophy decontextualized unproductive, leads the philosopher to emphasize the importance of both manifestations of our culture, education and philosophy, are formulated in terms of the crisis, analyzing the causes of it and served in the horizon of a new culture. The teaching of philosophy must respond to this context having as its goal for those involved in it are able to reflect and act real. It is necessary therefore to determine the characteristics that must assume the teaching of philosophy taking into account the processes of personalization and socialization that involves all education, and their inclusion in what has been called Salazar Bondy raised education.